Evaluation methods of out-of-autoclave epoxy prepreg working life used in aerospace application - de Faria Gonzales Leal, Tanila Penteado [UNESP]; de Paula Santos, Luis Felipe [UNESP]; Leali Costa, Michelle [UNESP]; Botelho, Edson Cocchieri [UNESP] (Taylor & Francis, 2024)
Prepregs are highly dependent on the resin, its chemical composition, and physical properties. Resin is the perishable part of prepreg materials and usually requires controlled storage, otherwise, its processability and properties may be affected. Oven curing prepregs are recognized to have longer life out of the freezer than those designed to cure in autoclave, and one of them, prepreg 2511, is the focus of this research. Prepreg 2511 has a formal out-time limit of 28 days at clean room environment (23°C/50% relative humidity), and 24 months shelf life, when frozen at −18°C, while common prepreg designed to be cured in autoclave, usually have 15 days of out-time and 12 months of shelf-life. It is known that the real shelf life and out time of epoxy-based materials tends to be longer than suppliers’ recommendation. Aiming to assess 2511 performance after those 28 days of exposure to clean room ambient, during and after 24 months in freezer; the material was exposed to this environmental condition for more than 28 days and tested periodically using different methods, including, Differential Scanning Calorimeter, High-Performance Liquid Chromatography tack, among others. In resume, the goal of this research was to identify 2511 longest out life without losing its properties and which of the tests used during these experiments would be more sensitive to capture its aging.
Keywords: out life; Out-of-autoclave prepreg; physical-chemical properties; thermal properties; thermosetting resin